Parkir di Kawasan Pasar Petisah Medan: Tinjauan Pengelolaan dan Kebijakan - Ahmad Nizar Simatupang; Morida Siagian; Dwi Lindarto Hadinugroho (Universitas Medan Area, 2022)
Traditional markets are places where sellers and buyers make transactions directly. Parking is one of the facilities that cannot be separated from traditional markets. In the traditional market of Petisah Medan, parking problems occur due to weak parking management. The purpose of this paper is to analyze the management and policy of good parking management in the Petisah Market area in order to create an orderly and orderly parking area. The research method in this writing is a qualitative method. The qualitative method is carried out by field observations by taking photos of documentation to explain how parking management is at Petisah Market. The results showed that the Petisah market has several parking locations with the type of parking consisting of on-street parking (On-Street Parking) and off-street parking (Off-Street Parking) located in the basement of Petisah Market. A good parking management policy in the Petisah Market area in order to create an orderly and orderly parking area is referring to the Medan Mayor Regulation Number 50 of 2014 concerning Parking Implementation in article 15.